2007
DOI: 10.1016/j.cell.2007.08.040
|View full text |Cite
|
Sign up to set email alerts
|

The Retromer Protein VPS29 Links Cell Polarity and Organ Initiation in Plants

Abstract: A key feature of plants (as opposed to animals) is their ability to establish new organs not only during embryogenesis, but also throughout their development. A master regulator of organ initiation in plants is the phytohormone auxin. Auxin acts locally as a morphogen and is directionally transported from cell to cell by polarized auxin efflux carriers, termed PIN-FORMED (PIN) proteins. Here we report that the Arabidopsis ortholog of the yeast and mammalian vacuolar protein sorting 29 (VPS29), a member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
278
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(292 citation statements)
references
References 40 publications
10
278
4
Order By: Relevance
“…However, polarization of PIN2 in epidermal and lateral root cap cells is independent of this pathway (Rahman et al, 2010). Recycling and intracellular trafficking of PIN2 require the retromer proteins SNX1 and VACUOLAR PROTEIN SORTING29 (VPS29) (Jaillais et al, 2006(Jaillais et al, , 2007. SNX1 and VPS29, which reside in late endosomes, are thought to be necessary for retrieval of PIN2 from late endosomes and thus prevent it from being internalized into lytic vacuoles (Kleine-Vehn et al, 2008).…”
Section: Snx1-dependent Endosomal Pathway Regulates Intracellular Auxmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polarization of PIN2 in epidermal and lateral root cap cells is independent of this pathway (Rahman et al, 2010). Recycling and intracellular trafficking of PIN2 require the retromer proteins SNX1 and VACUOLAR PROTEIN SORTING29 (VPS29) (Jaillais et al, 2006(Jaillais et al, , 2007. SNX1 and VPS29, which reside in late endosomes, are thought to be necessary for retrieval of PIN2 from late endosomes and thus prevent it from being internalized into lytic vacuoles (Kleine-Vehn et al, 2008).…”
Section: Snx1-dependent Endosomal Pathway Regulates Intracellular Auxmentioning
confidence: 99%
“…The direction of auxin flow largely depends on the polar localization of PIN proteins. It has been demonstrated that the polar targeting of a subset of PIN proteins (e.g., PIN1 and PIN2) is regulated by various protein trafficking pathways, including ADP ribosylation factor GTP-exchanging factor-dependent clathrinmediated internalization, Rab GTPases, and retromer complexmediated endosomal pathways (Geldner et al, 2001;Jaillais et al, 2006Jaillais et al, , 2007Michniewicz et al, 2007;Kleine-Vehn et al, 2008). The dynamic trafficking process that contributes toward facilitating the polar targeting of the newly synthesized nonpolar PINs to the plasma membrane (Dhonukshe et al, 2008) can be modified following physiological or environmental changes, resulting in the formation of altered intracellular auxin gradient as well as redirection of auxin flow (Paciorek et al, 2005;Laxmi et al, 2008;Shibasaki et al, 2009;Wan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…VSRs play a crucial role in sorting soluble proteins at the TGN and recycle from the PVC to the TGN (Li et al, 2002;Tse et al, 2004;Kim et al, 2010), although a recent study proposed that VSRs recycle from the TGN to the ER, where they are involved in sorting vacuolar proteins (Niemes et al, 2010a). Arabidopsis VPS29 is a component of the retromer complex (Oliviusson et al, 2006;Shimada et al, 2006;Jaillais et al, 2007), which is thought to be responsible for recycling VSRs (Oliviusson et al, 2006). Initially, the localization of VSR1 was examined in protoplasts from mag1-1 plants.…”
Section: Vsr1 Does Not Efficientlymentioning
confidence: 99%
“…Seedlings of wild-type Col-0 and all mutant lines: pat4-1 (EMS mutant), pat4-2 (AP-3 δ SALK mutant; At1g48760; [57]), pat2-2 (AP-3 β SAIL mutant; At3G55480, [10]), vps29 (At3g47810, [58]), double mutant line pat4-2 × pat2-2, crossed lines: pat4-1 × PIN2-GFP, pat4-1 × PIP2a-GFP, pat4-1 × BRI1-GFP, pat4-1 × GFPRABF2b, GFP tagged lines: PIN1 pro :PIN1-GFP (At1g73590, [59]), PIN2 pro :PIN2-GFP (At5G57090; [21]), 35S pro :PIP2a-GFP (X75883, [22]), BRI1 pro :BRI1-GFP (AT4G39400, [23]), RABF2b pro :GFPRABF2b (AT4g19640, [34]), AP-3 β pro :AP-3 β-GFP (At3G55480, [10]), AP-3 δ pro :AP-3 δ-GFP (At3G55480, [56]), as well as obtained by Gateway-based cloning strategy transgenic lines: fulllength Atµ3 (At1g56590) and the (18 amino acids truncated) dominant negative version were grown vertically in Petri dishes on 0.8% agar 0.5× Murashige and Skoog (MS) medium containing 1% sucrose (pH 5.9) at 18 °C, long-day photoperiod.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%